Analisis Literatur: Penerapan Model Kooperatif Tipe Teams Games Tournamet Terhadap Hasil Belajar IPS Di Sekolah Dasar - Dita Amelia Asshiba; Yustia Suntari; Chrisnaji Banindra Yudha (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2025)
Social Studies learning at the elementary school level plays an important role in shaping students’ cognitive and social skills. This article presents a descriptive analytical literature review to assess the effect of the Teams Games Tournament (TGT) learning model on elementary school students’ social studies learning outcomes. This study collected and processed secondary data from various articles, journals, and research reports that discussed the implementation of TGT in elementary schools. Most of the findings indicate that the implementation of TGT consistently increases the average IPS score, improves material absorption, and increases the percentage of learning completion. The effectiveness of this model is triggered by a combination of educational game elements, teamwork, and healthy competition that motivate students to be actively involved. Although variations in results arise due to differences in teacher readiness, content suitability, and classroom management, overall evidence supports TGT as a viable alternative strategy to improve the quality of IPS learning. This study also encourages further research to explore the long-term effects of TGT on students’ critical thinking skills and character development